Standardization and best practices in single-cell testing for liquid alkaline water electrolysis - Shviro, Meital; Kang, Sun Young; Campos, Fernando Diaz; Larson, Virginia; Maurya, Sandip; Leonard, Daniel Philip (Frontiers in Energy Research, 2025)
The increasing demand for efficient and sustainable hydrogen production has driven significant advancements in water electrolysis technologies. Among these, liquid alkaline water electrolysis (LAWE) stands out for its cost-effectiveness and scalability. This manuscript establishes best practices and standardized testing procedures for single-cell LAWE, focusing on the use of nickel foam as both anode and cathode substrates, while incorporating catalysts such as nickel-iron layered double hydroxide (NiFe-LDH) as the anode material and nickel-molybdenum on carbon (NiMo/C) as the cathode material. By providing detailed guidelines on material preparation, cell assembly, and performance evaluation, this work offers a comprehensive framework to improve reproducibility and ensure consistency. The results demonstrate that applying these best practices minimizes variability across different laboratories and experimental setups, laying the groundwork for more robust comparisons and accelerating progress in LAWE research.